2019
DOI: 10.28991/esj-2019-01200
|View full text |Cite
|
Sign up to set email alerts
|

Stock Price Reactions on NASDAQ Stock Exchange for Special Dividend Announcements

Abstract: Announcing dividend pay-out policy by a company will signals market firm's future prospects and changes its stock prices according to dividend signalling theory. By analysis the effect of special dividend announcements for 5 companies listed in NASDAQ for the period of 2014-2018, this study investigates the stock price reactions to special dividend announcement for 40 days around the event and challenges dividend signalling theory. The empirical results calculated both in discrete and logarithmic forms. Only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…Dhungel (2013) found that share price of most of the banks in Nepal is not significantly impacted by dividends. Seyedimany (2019) showed that shareholders are not in a position to gain value from the announcements of special dividend in NASDAC, which is in consistent with the dividend irrelevance hypothesis of Miller and Modigliani (1961) Alaeto (2018) found that dividend announcements fail to impart any information to react stock prices of firms listed on London Stock Exchange (LSE), which is in support of the M-M Dividend Irrelevance Theory. Allen and Rachim (1996) found no evidence that dividend yield is correlated with stock price volatility of Australian listed companies.…”
Section: Review Of Empirical Literaturementioning
confidence: 53%
“…Dhungel (2013) found that share price of most of the banks in Nepal is not significantly impacted by dividends. Seyedimany (2019) showed that shareholders are not in a position to gain value from the announcements of special dividend in NASDAC, which is in consistent with the dividend irrelevance hypothesis of Miller and Modigliani (1961) Alaeto (2018) found that dividend announcements fail to impart any information to react stock prices of firms listed on London Stock Exchange (LSE), which is in support of the M-M Dividend Irrelevance Theory. Allen and Rachim (1996) found no evidence that dividend yield is correlated with stock price volatility of Australian listed companies.…”
Section: Review Of Empirical Literaturementioning
confidence: 53%
“…A study by Bustani et al (2021) confirmed the significant impact of earning per stock and dividend payout ratio on stock prices of companies belonging to food and beverage sector at Indonesia Stock Exchange for a period of five years (2014–2018). Seyedimany (2019) investigated companies listed on NASDAQ for the period of 2014–2018 and found that the dividend announcement has no significant impact on stock price for the companies listed on NASDAQ. Syofyan et al (2020) investigated the companies listed on the Indonesia Stock Exchange in the period 2008–2010 and found that stock prices have significant positive relation with the dividend policies of the companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, while planning a project, the managers asses the risk factors of different components including inventory management. In this context, we refer the interested readers to the current works of Mitsumori [34], Seyedimany [41], and Baylan [4].…”
Section: Literature Reviewmentioning
confidence: 99%